Venture capital - Sapienza, Harry J., 1949-; Wright, Mike, 1952-; Busenitz, Lowell W., 1952- (Cheltenham, UK ; Northampton, MA : Elgar, 2003)
The aims of this collection are to identify contributions to venture capital market and in academic research relating to this market from the 80s and 90s; and to reflect the growing multi-disciplinary of reseach on venture capital.
Includes bibliographical references and indexes.
oif 23/03/15
Loan
Keywords: Venture capital